Peran Orang Tua dan Guru dalam Membentuk Pendidikan Berkarakter pada Anak Desa Bah Jambi - Haqqy Tamimah; Muhammad Rofi Halmi; Ratih Pebrianti; Rigi Septiandi; Yulita Cita Aggini (MODELING: Jurnal Program Studi PGMI, 2023)
Parents play an important role in developing the potential of their children. Parents are the first nahdatul ulum (educators) in the family environment. Parents must be sensitive that a child has great potential for his development. Parents must instill good character values ​​in their children, such as honesty, democratic religiosity, fairness, trustworthiness, responsibility, humility, discipline, independence, and empathy. Parents educate character through good influence. Setting a good example and providing useful education to achieve this requires maximum efforts from parents to educate and instill useful characters for children. The responsibility of educating children does not only come from within the family, but also outside the family environment such as teachers. Teachers also have a great responsibility in providing character education to children, which is in accordance with the needs of their students. In this study, it is shown that the role of parents is very influential with the character of the child and the teacher is also very much needed by the child to meet a capable character.